2013
DOI: 10.3109/09553002.2014.868616
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-laboratory comparison of a multibiodosimetric approach to triage in a simulated, large scale radiation emergency

Abstract: The data demonstrate that the MULTIBIODOSE approach of applying multiparametric tools to radiation emergencies is valid and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…When a new dosimetry technique is proposed, it is necessary to develop, test and then validate the method before it can be said to reach a sufficient standard for inclusion as a fully operational dosimetry method. Inter-comparison exercises are a recognised method for validating tools and techniques within the field of biological and physical retrospective dosimetry (Badie et al 2013;Romm et al 2013;Ainsbury et al 2014;Abend et al 2016).…”
Section: Integration Of New Biological and Physical Retrospective Dosmentioning
confidence: 99%
“…When a new dosimetry technique is proposed, it is necessary to develop, test and then validate the method before it can be said to reach a sufficient standard for inclusion as a fully operational dosimetry method. Inter-comparison exercises are a recognised method for validating tools and techniques within the field of biological and physical retrospective dosimetry (Badie et al 2013;Romm et al 2013;Ainsbury et al 2014;Abend et al 2016).…”
Section: Integration Of New Biological and Physical Retrospective Dosmentioning
confidence: 99%
“…Timed intercomparisons have been described by Rothkamm et al (2013a) and Ainsbury et al (2014) with triage dose estimates, based on foci counts in 50 cells, reported within 7 h (10 samples) and 3 h (8 samples), respectively. With a more rapid processing technique and scoring just 20 cells it may be possible to produce dose estimates for 96 samples in 7-11 h (Moquet et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With a more rapid processing technique and scoring just 20 cells it may be possible to produce dose estimates for 96 samples in 7-11 h (Moquet et al 2014). Past experience (Rothkamm et al 2013a;Ainsbury et al 2014) and the first inter-comparison have shown that for rapid triage purposes, i.e. detection of moderate to high doses, manual scoring of 50 cells or 200 cells scored automatically, is fully sufficient and even scoring 20 cells manually or 50 automatically, may be sufficiently accurate in a triage setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, it may be imperative to screen tens or hundreds of thousands of individuals for radiation exposure, both to identify and prioritize individuals that would benefit from medical treatment and to alleviate the concerns of the “worried well” (35). The threat of large-scale radiological incidents has led to a number of recent developments in the fields of biological and physical dosimetry (6). However, to triage potentially large numbers of people exposed to ionizing radiation, the development of high-throughput approaches for radiation biodosimetry has been identified as a high priority.…”
Section: Introductionmentioning
confidence: 99%